BENTENG CEPURI KOTAGEDE SEBAGAI SUMBER BELAJAR SEJARAH DALAM MATA PELAJARAN IPS - Arrazaq, Naufal Raffi; Hasan, Renol; Tasnur, Irvan (Universitas Negeri Semarang, 2023)
Kajian mengenai Benteng Cepuri sebagai sumber belajar sejarah pada mata pelajaran IPS belum dilakukan secara mendalam oleh peneliti terdahulu. Tujuan penelitian ialah menganalisis keterkaitan Benteng Cepuri Kotagede dengan mata pelajaran IPS. Metode penelitian ialah kualitatif dengan data studi pustaka. Analisis data dilakukan dengan menguraikan data Benteng Cepuri Kotagede dan dikaitkan Kompetensi Dasar (KD) mata pelajaran IPS. Hasil penelitian menunjukkan bahwa Benteng Cepuri Kotagede berpotensi digunakan sebagai sumber belajar sejarah dalam mata pelajaran IPS. Benteng Cepuri Kotagede memiliki keterkaitan dengan mata pelajaran IPS kelas VII SMP/MTs KD 3.4., yang mengulas kronologi kehidupan Bangsa Indonesia masa Islam. Salah satu peninggalan masa Islam ialah Benteng Cepuri Kotagede dari masa Kerajaan Mataram Islam. Pendidik dapat mengkaitkan antara KD, indikator, dan tujuan pembelajaran IPS dengan nilai-nilai kesejarahan dan arkeologi Benteng Cepuri Kotagede. Materi yang dapat dikembangkan dari Banteng Cepuri Kotagede ialah tata kota, teknologi, riwayat bencana, serta pelestarian peninggalan sejarah dan arkeologi. The study of Cepuri Fort in Kotagede as a source of historical learning in social studies subjects has not been carried out in depth by previous researchers. The purpose of the study was to analyze the relationship between Cepuri Fort in Kotagede and social studies subjects. The research method is qualitative with literature study data. Data analysis was carried out by outlining the data of Cepuri Fort in Kotagede and attributed it to the basic competencies (KD) of social studies subjects. The results showed that Cepuri Fort in Kotagede has the potential to be used as a source of learning history in social studies subjects. Cepuri Fort in Kotagede is related to the social studies class VII subject of SMP/MTs KD 3.4., which reviews the chronology of the life of the Indonesian nation during the Islamic period. One of the relics of the Islamic period is the Cepuri Fort in Kotagede from the time of the Mataram Islam Kingdom. Educators can relate the KD, indicators, and objectives of social studies learning with the historical and archaeological values of Cepuri Fort in Kotagede. The materials that can be developed from Cepuri Fort in Kotagede are urban planning, technology, disaster history, and preservation of historical and archaeological relics.